A Simple Spectrophotometric Determination of Phosphate in Sugarcane Juices, Water and Detergent Samples - Mahadevaiah; M. S. Yogendra Kumar; Mansour S. Abdul Galil; M. S. Suresha; M. A. Sathish; G. Nagendrappa (E-Journal of Chemistry)
A simple spectrophotometric method is developed for the determination of phosphate in sugar cane juice, water and detergent samples. The method is based on the formation of phosphomolybdate with added molybdate followed by its reduction with sodium sulphide in aqueous sulfuric acid medium. The system obeys Lambert-Beer’s law at 715 nm in the concentration range 0.3-12.24 ppm. Molar absorptivity, correlation coefficient and Sandell’s sensitivity values were found to be 6.1x103 mol-1 cm-1, 0.999 and 0.0156 µg cm-2 respectively. The results obtained were reproducible with acceptable standard deviation 3.7% and relative error 3.4%. For a comparison of the method phosphate present in various samples were also determined separately following an official method. The results of the developed method compare well with those of the official method.